2016
DOI: 10.1016/j.conctc.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Study design of a cluster-randomized controlled trial to evaluate a large-scale distribution of cook stoves and water filters in Western Province, Rwanda

Abstract: BackgroundIn Rwanda, pneumonia and diarrhea are the first and second leading causes of death, respectively, among children under five. Household air pollution (HAP) resultant from cooking indoors with biomass fuels on traditional stoves is a significant risk factor for pneumonia, while consumption of contaminated drinking water is a primary cause of diarrheal disease. To date, there have been no large-scale effectiveness trials of programmatic efforts to provide either improved cookstoves or household water fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…34,35 A pair of randomised controlled trials found little statistical evidence of a reduction in pneumonia incidence with provision of chimneys 36 or cleaner burning cookstoves, 37 and several more studies investigating household air pollution and childhood pneumonia are in progress. 38,39 This suggests that the provision of chimneys or cleaner burning practices does not result in a sufficient reduction of air pollution to translate into a reduction in health effects. This finding is consistent with the analysis and recommendations by the WHO guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 A pair of randomised controlled trials found little statistical evidence of a reduction in pneumonia incidence with provision of chimneys 36 or cleaner burning cookstoves, 37 and several more studies investigating household air pollution and childhood pneumonia are in progress. 38,39 This suggests that the provision of chimneys or cleaner burning practices does not result in a sufficient reduction of air pollution to translate into a reduction in health effects. This finding is consistent with the analysis and recommendations by the WHO guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The IMCI-pneumonia assessment protocol is a common diagnostic criterion for the classification and treatment of childhood pneumonia at health facilities in Ethiopia [21]. The Ethiopian Demographic and Health Survey (EDHS) [7] and other similar studies conducted in different parts of the world also used this diagnostic criterion for childhood pneumonia assessment; such as the randomized controlled trials conducted in Malawi [22], Rwanda [23], Ghana [24], Indian [25] and Guatemala [26]. In this study, we used the term childhood ALRI as a synonym for the IMCI-pneumonia, because the term childhood ALRI is the preferred expression for childhood pneumonia in peculiar to the developing world countries [27].…”
Section: Introductionmentioning
confidence: 99%
“…We undertook this study in the context of a large-scale clusterrandomized controlled trial (CRT) described elsewhere. 25 We aimed to assess the effectiveness of a point-of-use water filter on seroconversion against a panel of viral, bacterial, and protozoan enteropathogens among young children. We also sought to explore the potential for using serologic response as an objective alternative to reported diarrhea to assess the effectiveness of water quality interventions, an approach that has been advocated in other serologic studies.…”
Section: Introductionmentioning
confidence: 99%